The Influence of Infrastructure and Teachers’ Work Motivation on the Teachers’ Professionalism - Didik Saputra; Syaiful Eddy; Neta Dian Lestari (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of educational facilities and infrastructure, as well as teachers’ work motivation, on the professionalism of public junior high school teachers in Suak Tapeh District. Employing a quantitative ex post facto approach, the research surveyed all 105 teachers from three state schools using validated questionnaires, with data analyzed via simple and multiple regression in SPSS. The results demonstrate that both factors have a significant positive influence: facilities account for 25.3% of the variance in professionalism, while work motivation explains 28.8%. Their combined simultaneous influence contributes 28.7%. The novelty of this study is its localized focus, integrating these two critical variables into a single empirical model within a specific Indonesian district context. A key practical implication is that school administrators and policymakers must adopt a dual strategy, concurrently improving physical infrastructure and implementing programs to enhance intrinsic teacher motivation to effectively raise professional standards. This research contributes by providing empirical evidence of these interconnected relationships and offering a targeted framework for improving educational quality in similar regional settings.